Role of Tonsillectomy in the Management of Carcinomas of Unknown Primary of the Head and Neck: A Retrospective Study Based on p16 Analysis - Podeur, Pauline; Mancini, Julien; Delgrande, Jean; Santini, Laure; Salas, Sébastien; Wong, Stéphanie; Giovanni, Antoine; Dessi, Patrick; Michel, Justin; Radulesco, Thomas; Fakhry, Nicolas (Frontiers in Oncology, 2020)
Purpose To evaluate the impact of tonsillectomy on the detection of the primary tumor, based on p16 immunohistochemistry analysis, in patients with cervical unknown primary of squamous cell carcinoma (SCC-CUP). Methods This was a retrospective study of 63 patients, included from January 2008 to December 2017 in a single institution. All patients had an initial assessment with physical examination, CT scan of the neck and chest, whole body FDG-PET CT, and endoscopy under general anesthesia, which failed to determine the primary tumor. Results Forty-seven out of the 63 patients had an ipsi- or bilateral tonsillectomy which revealed 12 tonsil cancers (26%). The tonsil primary was ipsilateral to positive nodes in 10 cases, contralateral in 1 case and, in 1 case, the patient had bilateral neck involvement. The analysis of the p16 status was carried out in 41/63 patients (65%). Among the 32 patients who had a p16 analysis and tonsillectomy, the rate of primary detection was 59% (10/17) for p16-postives and 0% (0/15) for p16-negatives (p < 0.001). Conclusion These results suggest that an extended work-up should be systematically proposed including bilateral tonsillectomy (+/- mucosectomy of the base of tongue) in SCC-CUP p16-positive patients but not in p16-negatives.